Inhibitory Effect of Fermented Flammulina velutipes Polysaccharides on Mice Intestinal Inflammation - Ma, Sheng; Xu, Jianxiong; Lai, Ting; Xu, Weina; Zhang, Jing; Zhang, Hongcai; Zhang, Weiyi (Frontiers in Nutrition, 2022)
In this work, to investigate the effect of Flammulina velutipes polysaccharides (FVP) on mice intestinal inflammation, FVP were extracted from Flammulina velutipes (FV) using a solid anaerobic fermentation technique. The antioxidant and anti-inflammatory capacities of FVP and fermented FVP (FFVP) induced by lipopolysaccharide (LPS) were investigated in vitro and in vivo. The results showed that yield of FFVP (9.44%) was higher than that of FVP (8.65%), but the molecular weight (MW) of FFVP (15702 Da) was lower than that of FVP (15961 Da). The antioxidant and anti-inflammatory capacities of FFVP were higher than that of FVP in preventing the mice diarrhea, enhancing antioxidant capacities and reducing the secretion and mRNA expression of IL-1β, IL-6, IL-18, and TNF-α. The anti-inflammatory mechanisms of FVP and FFVP were analyzed by inhibiting the activation of NLRP3 signaling pathway using an LPS-induced mice model. This study indicated that FFVP could be used as a functional antioxidant, indicating a potential application in functional food and health products.